Analysing the physical and mechanical characteristics of soft clay reinforced with polypropylene columns - Md. Ikramul, Hoque (2024)
The progression of infrastructure on soft soil is quite challenging due to the soils high compressibility, low bearing capacity and lateral deformation. Granular column techniques have the ability to decrease settlement in weak and soft soil by increasing the bearing capacity, and accelerating the dissipation of excessive pore water pressure. Moreover, soft soil's shear strength can be significantly improved through the employment of reinforcing columns by preventing the lateral deformation of the clay particle. . The main objective of this research is to investigate the impact of polypropylene columns on enhancing the shear strength and compressibility characteristics of soft reconstituted kaolin clay. The strength qualities were examined using the analysis of several aspects, such as the area replacement ratio, height penetration ratio, and volume replacement ratio. This examination encompassed both single and grouped polypropylene columns. Furthermore, the impact of confining pressure on the compressibility properties of polypropylene-reinforced kaolin clay was evaluated. One of the goals of this study is to provide a design chart that links the volume replacement ratio and mean normal effective stress to the undrained shear strength (Su) of polypropylene columns reinforced with kaolin clay by utilizing the critical state soil mechanics framework. The reinforced kaolin samples were assessed using the Unconfined Compression Test (UCT) and Consolidated Undrained (CU) Triaxial Test. The polypropylene columns' diameter and height as well as the effective confining pressure, σꞌ3 , were among the research factors. The analysis of the results was conducted by utilizing the Mohr-Coulomb and critical state failure criteria. Based on the UCT results, it was observed that the Su generally improved as the height penetrating ratio increased, however, once it reached 100% height penetrating ratio, it began to decrease. The area replacement ratio of polypropylene also affected the Su increment. The shear strength of the soil sample did not change despite its high area replacement ratio. As the soil sample's circumference was smaller than required, the column's shearing strength needed to be increased. The ratio increased as the strength increased in the absence of restricting pressure. Nonetheless, excessive area replacement decreased the shear strength of the sample reinforced by group columns as the remaining width of the soil sample became too narrow to sustain the columns. By using the Mohr-Coulomb failure criterion of the CU test findings, the effective friction angle remained relatively constant after inserting polypropylene columns. However, it did lead to an improvement in undrained shear strength and apparent cohesion of the kaolin clay. Additionally, it was demonstrated that the addition of polypropylene columns increased the pore water pressure's dissipation. Using the critical state soil mechanics framework, the analysis allowed for the determination of unique critical state parameters for each sample, which were M, Γ, and λ. For the soil-polypropylene composite, the majority of M values were found to fall between 1.18 and 1.30. This range is equivalent to a variation in the critical state friction angle, which ranged from 30° to 35°. As a result, the soil-polypropylene composite can be classified under the category of "mixtures of gravel and sand with fine-grained soils". In general, it can be concluded that the installation of polypropylene columns has the potential to improve the shear strength and compressibility characteristics of soft clay. Therefore, a design chart was developed with the purpose of working as a design tool, specifically for calculating the necessary volume of polypropylene that is required to create vertical columns that align with the desired shear strength of the improved clay soil.